PENGARUH MODEL PEMBELAJARAN DEBAT TERHADAP KETERAMPILAN MENYAMPAIKAN GAGASAN SISWA KELAS VII SMP SANTO YOSEPH MEDAN TAHUN PEMBELAJARAN 2024/2025 - Reslin; Liana; Candra Ronitua Gultom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify the skills of conveying ideas of class VII students by applying the Debate learning model. Sampling in this study was carried out using the Simple Random Sampling technique with the One Group Pretest Posttest Control Design research design so that class VII-C was obtained as the sample of this study. The number of class VII-C students was 34 students. The method used in this study used the experimental method, to see the effect of the Debate learning model on the skills of conveying ideas. The research instrument was used through tests and perception questionnaires that had been validated by experts. The normality test showed that the data was normally distributed with the results of the significance of the pretest data 0.200> 0.05 and the posttest data 0.121> 0.05. The results showed that the average value of the questionnaire was 4.43 with a scale of 5, the results showed a very positive perception. The average result (Mean) of the pretest was 60.17 while the posttest was 81.35 which was included in the very good category. This shows that there was a significant increase with a difference of 21.18. The data obtained were analyzed using the t-test. Based on the results of data analysis conducted from the pretest and posttest, the t-value obtained was 7.888> t-table of 1.692 and significance (0.000 <0.05). This shows that the hypothesis H1 is accepted and H0 is rejected, so it can be concluded that the use of the Debate learning model has an effect on the skills of conveying ideas of class VII students of SMP Santo Yoseph Medan in the 2024/2025 Academic Year.